Radiation of surface waves from a charge rotating around a dielectric cylinder; Journal of Instrumentation; Vol. 13 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-17) - Kotanjyan A. S.; Mkrtchyan A. R. Alpik Rafaelovich; Saharian A. A.; Kotanjyan V. Kh. (2018, 2018)
Title screen